Ẓihār and the Protection of Women's Dignity in Tafsir al-Aḥkām: An Analysis of Shaykh Ali al-Shabuni's Thought - Bayumi Asyji` Zaaidil Mubaarok (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This article examines the protection of women’s dignity within the regulation of Ẓihār through the interpretation of Shaykh Muhammad Ali al-Shabuni in Rawā’i‘ al-Bayān Tafsīr Āyāt al-Aḥkām min al-Qur’ān. This study argues that, beyond its juridical structure, Qur’an Surah al-Mujādilah verses 1–4 contain substantive protections for women that are consistent with contemporary feminist principles. This research employs a qualitative method using a descriptive-analytical library research approach, with Rawā’i‘ al-Bayān as the primary source and Islamic feminist literature and gender theory as secondary sources. Data were collected through documentary studies of the exegetical work and relevant literature, while data analysis employed thematic content analysis to identify the values of women’s dignity protection embedded in al-Shabuni’s interpretation. The findings demonstrate that although al-Shabuni’s interpretation is methodologically grounded in classical jurisprudence, it implicitly affirms three feminist values: the protection of women’s bodily dignity and marital status; procedural justice that provides women with an opportunity to raise grievances and have their voices heard; and structural limitations on patriarchal authority within the household. This article concludes that the regulation of Ẓihār should not be understood merely as a punitive mechanism, but rather as an early Qur’anic corrective to the misogynistic practices of the pre-Islamic era (Jāhiliyyah). Accordingly, it provides a textual basis for the reinterpretation of Islamic family law toward a more gender-just framework.